Thermal Physiology and Local Responses of Human Body During Exercise in Hot Conditions (Journal of Fiber Bioengineering and Informatics, 2012)
Body temperature is maintained by effective thermoregulation, which depends on heat balance thatincludes heat production and heat loss. Skin moisture and water evaporation from the body playan important role in heat transfer, especially during exercising or in hot conditions. The regionalskin evaporation can significantly affect the heat release of the each body part, the pattern of skintemperature distribution and the thermoregulation. Indeed, the distribution of sweat evaporationand skin temperature can also be applied as a means of managing the body thermoregulation. Thisstudy reviews the thermoregulation of human body, local skin evaporation and the skin temperaturedistribution. It also highlights the implication of local skin evaporation and skin temperature in thedevelopment of sportswear and the prevention of heat disorder in hot conditions.